Poverty levels and poverty alleviation policy on the urban periphery - Nkosi, Noluthando Sinethemba (My University, 2022)
The urban poor living on the periphery face unique challenges due to their location. The purpose of this study is to outline the povertyalleviation policies and to explore the conditionson the urban periphery. The focus is Lufhereng, a recently developed residential area in the City of Johannesburg. The extent of poverty in the area is assessed using descriptive data from The Living the Urban Periphery survey (2016 –2019) using the South African Index of Multiple Deprivation poverty indicators. A policy review on poverty alleviation policies and key respondent interviews are also conducted to determine how these policies by government addresspoverty in urban peripheries and in Lufhereng.Key findings from this study show thatpoverty alleviation policies are not specific to the urban periphery. While access tohousing and services improved for residents, Lufherengstill faces high rates of unemployment, exacerbated by being situated far from areas of employment, limited transport systems and lack of economic development in the area.
A research report submitted to the Faculty of Engineering and The Built Environment, University of The Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science (Development Planning), 2022